Detoxification and oxidative stress responses along with microcystins accumulation in Japanese quail exposed to cyanobacterial biomass - Pasková, Veronika; Adamovský, Ondrej; Pikula, Jirí; Skocovská, Blanka; Band'ouchová, Hana; Horáková, Jana; Babica, Pavel; Marsálek, Blahoslav; Hilscherová, Klára (The Science of the total environment, 2008)
The cyanobacterial exposure has been implicated in mass mortalities of wild birds, but information on the actual effects of cyanobacteria on birds in controlled studies is missing. Effects on detoxification and antioxidant parameters as well as bioaccumulation of microcystins (MCs) were studied in birds after sub-lethal exposure to natural cyanobacterial biomass. Four treatment groups of model species Japanese quail (Coturnix coturnix japonica) were exposed to controlled doses of cyanobacterial bloom during acute (10 days) and sub-chronic (30 days) experiment. The daily doses of cyanobacterial biomass corresponded to 0.2-224.6 ng MCs/g body weight. Significant accumulation of MCs was observed in the liver for both test durations and slight accumulation also in the muscles of the highest treatment group from acute test. The greatest accumulation was observed in the liver of the highest treatment group in the acute test reaching average concentration of 43.7 ng MCs/g fresh weight. The parameters of detoxification metabolism and oxidative stress were studied in the liver, heart and brain. The cyanobacterial exposure caused an increase of activity of cytochrome P-450-dependent 7-ethoxyresorufin O-deethylase representing the activation phase of detoxification metabolism. Also the conjugation phase of detoxification, namely the activity of glutathione-S-transferase, was altered. Cyanobacterial exposure also modulated oxidative stress responses including the level of glutathione and activities of glutathione-related enzymes and caused increase in lipid peroxidation. The overall pattern of detoxification parameters and oxidative stress responses clearly separated the control and the lowest exposure group from all the higher exposed groups. This is the first controlled study documenting the induction of oxidative stress along with MCs accumulation in birds exposed to natural cyanobacterial biomass. The data also suggest that increased activities of detoxification enzymes could lead to greater biotransformation and elimination of the MCs at the longer exposure time.
Keywords: Coturnix; bakteriální toxiny; glutathionreduktasa; cytochrom P-450 CYP1A1; chemické látky znečišťující vodu; látky reagující s kyselinou thiobarbiturovou; glutathionperoxidasa; Oxidative Stress; Animals; Myocardium; Thiobarbituric Acid Reactive Substances; Biomass; glutathion; oxidační stres; Cytochrome P-450 CYP1A1; myokard; prsní svaly; Liver; Cyanobacteria; Glutathione Reductase; mozek; zvířata; Microcystins; biomasa; Glutathione; glutathiontransferasa; Glutathione Peroxidase; Brain; sinice; Pectoralis Muscles; játra; Glutathione Transferase; Water Pollutants, Chemical; Bacterial Toxins; mikrocystiny